2011
DOI: 10.1530/rep-10-0266
|View full text |Cite
|
Sign up to set email alerts
|

Formation of nucleoli in interspecies nuclear transfer embryos derived from bovine, porcine, and rabbit oocytes and nuclear donor cells of various species

Abstract: The most successful development of interspecies somatic cell nuclear transfer (iSCNT) embryos has been achieved in closely related species. The analyses of embryonic gene activity in iSCNT embryos of different species combinations have revealed the existence of significant aberrations in expression of housekeeping genes and genes dependent on the major embryonic genome activation (EGA). However, there are many studies with successful blastocyst (BL) development of iSCNT embryos derived from donor cells and ooc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
43
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 61 publications
2
43
0
Order By: Relevance
“…It has been reported that, in some iSCNT embryos, nucleoli were not formed and development was arrested depending on the species of the cell donor and oocyte [13]. We examined the formation of nucleoli in raccoon dog iSCNT embryos by anti-nucleolin (C23) antibody labeling.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been reported that, in some iSCNT embryos, nucleoli were not formed and development was arrested depending on the species of the cell donor and oocyte [13]. We examined the formation of nucleoli in raccoon dog iSCNT embryos by anti-nucleolin (C23) antibody labeling.…”
Section: Discussionmentioning
confidence: 99%
“…It is present primarily in nucleoli with active RNA polymerase I. All these attributes make nucleolin an ideal marker of nucleoli [13]. …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations